The Behind Closed Lenses: Analyzing the Efficacy of Personal Data Protection Laws in Combatting Hidden Cameras - Weley, Nadia Carolina; Amboro, Florianus Yudhi Priyo; Seroja, Triana Dewi (Universitas Internasional Batam, 2024)
This study explores the effectiveness of personal data protection against hidden camera recordings in Batam City, which are used to identify a person and used for personal purposes, a problem in Indonesia despite the issuance of Act Number 27 of 2022 on Personal Data Protection. This research focuses on the aspects of legal protection and sanctions received by perpetrators of personal data and privacy sharing crimes; this study also identifies the challenges and opportunities Indonesian people face regarding their privacy in public places. The concept of personal data protection is analyzed through an empirical legal research method with a descriptive-qualitative approach, considering the current Indonesian legal framework. This research also involves Soerjono Soekanto's Theory of Legal Effectiveness and Chambliss and Seidman's Theory of the Working of Law, which will assist in elaborating the research. This research highlights the importance of public awareness and the role of supervisory agencies in addressing the risks of privacy-infringing camera recordings. The results show the need for a collaborative strategy between the government and society to strengthen personal data protection. The results of this study can assess the effectiveness of the enforcement of the PDP Law in Batam City through five factors and how the regulation in Indonesia overshadows the problems faced, such as the lack of law enforcement roles in Batam City and the lack of reminders such as facilities that can be a bridge for the public to know the prohibition of installing hidden cameras in public places that can endanger the public.